Plexiform neurofibroma with neurofibromatosis type I/ von Recklinghausen's disease: A rare case report. (September 2020) - Poswal, Pooja; Bhutani, Namita; Arora, Sunil; Kumar, Raj
Abstract: Introduction: Plexiform neurofibroma with neurofibromatosis type 1 (NF1) or Von Recklinghausen's disease is a rare entity and occurs in approximately 5–15% patients. These are slow growing, painless and locally infiltrating tumors. The pattern of inheritance is autosomal dominant and its penetrance is almost complete by 5 years of age. Presentation of case: We hereby report a case of 13 years old boy visited presenting with swelling of right eyelid and forehead. After surgical removal, the tissue was sent for histopathological evaluation. Microscopy revealed an unencapsulated tumor mass comprising of well organized mixture of multiple nerve bundles with interlacing neural tissue in background of spindle shaped cells along with myxoid areas and numerous blood vessels. Discussion: The NF1 gene responsible for the disease is located on chromosome 17 at locus 17q11.2 that codes for the protein neurofibromin. The frequency of neomutations is particularly high and almost half of the cases are sporadic. NF1 is characterized by a wide variability of clinical expressions, even within a given family. Majority of patients can be diagnosed only after thorough physical examination. Conclusion: The wide variation of the clinical expression, the tumor risk and the totally unpredictable evolution of the disease impose regular monitoring of NF1 patients. This surveillance is mainly clinical and has to be adapted to the patient's age in order to assure early management of complications. Highlights: Plexiform neurofibroma with neurofibromatosis type 1 is a rare entity. The presentation of patients with NF-1 is extremely variable. Early diagnosis is crucial for patient to prevent further complications of the disease. Psychological counseling and long term follow up is mandatory to improve quality of life.